2022
DOI: 10.1038/s41598-022-15861-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered genome-wide hippocampal gene expression profiles following early life lead exposure and their potential for reversal by environmental enrichment

Abstract: Early life lead (Pb) exposure is detrimental to neurobehavioral development. The quality of the environment can modify negative influences from Pb exposure, impacting the developmental trajectory following Pb exposure. Little is known about the molecular underpinnings in the brain of the interaction between Pb and the quality of the environment. We examined relationships between early life Pb exposure and living in an enriched versus a non-enriched postnatal environment on genome-wide transcription profiles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…In a recent publication from our group, we described relationships between early life lead exposure and living in an enriched vs. a nonenriched postnatal environment on adult genome-wide transcription profiles in the CA1 region of the hippocampus of rats. 18 In this RNA-sequencing study, we found that expression of genes was differentially affected by early postnatal lead exposure and that environmental enrichment further modified the lead-altered transcriptome. “Minimal significant differential gene expression changes were observed as a consequence of living in the enriched environment in normal control animals and the transcriptome of lead-exposed enriched animals was indistinguishable from that of non–lead-exposed control enriched animals.” Remarkably, we also found that living in the enriched environment largely reversed the vast majority of lead-induced alterations to the hippocampal transcriptome.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…In a recent publication from our group, we described relationships between early life lead exposure and living in an enriched vs. a nonenriched postnatal environment on adult genome-wide transcription profiles in the CA1 region of the hippocampus of rats. 18 In this RNA-sequencing study, we found that expression of genes was differentially affected by early postnatal lead exposure and that environmental enrichment further modified the lead-altered transcriptome. “Minimal significant differential gene expression changes were observed as a consequence of living in the enriched environment in normal control animals and the transcriptome of lead-exposed enriched animals was indistinguishable from that of non–lead-exposed control enriched animals.” Remarkably, we also found that living in the enriched environment largely reversed the vast majority of lead-induced alterations to the hippocampal transcriptome.…”
mentioning
confidence: 95%
“…“Minimal significant differential gene expression changes were observed as a consequence of living in the enriched environment in normal control animals and the transcriptome of lead-exposed enriched animals was indistinguishable from that of non–lead-exposed control enriched animals.” Remarkably, we also found that living in the enriched environment largely reversed the vast majority of lead-induced alterations to the hippocampal transcriptome. 18 Animals raised in the enriched environment also had no memory deficit, whereas animals raised in a nonenriched environment had a lead-induced memory deficit. Further, “the biological, cellular, or molecular processes that were downregulated due to lead exposure were upregulated by environmental enrichment and vice versa.” 18 The expression of a large number of genes involved in synaptic transmission, plasticity, cytoskeletal regulation, and transcriptional regulation, as well as epigenetic regulators and long noncoding RNAs, were altered by lead exposure, and environmental enrichment, for the most part, reversed these lead exposure-induced alterations in expression.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…For example, preclinical studies on the benefits of these types of enriching interventions on reversing lead-induced learning deficits have uncovered neurobiological mechanism(s) by which they benefit the lead-exposed brain. 22 , 23 …”
mentioning
confidence: 99%